Absence of mind : the dispelling of inwardness from the modern myth of the self - Robinson, Marilynne (Terry lectures., 2010)
"In this ambitious book, acclaimed writer Marilynne Robinson applies her astute intellect to some of the most vexing topics in the history of human thought-- science, religion, and consciousness. Crafted with the same care and insight as her award-winning novels, Absence of Mind challenges postmodern atheists who crusade against religion under the banner of science. In Robinson's view, scientific reasoning does not denote a sense of logical infallibility, as thinkers like Richard Dawkins might suggest. Instead, in its purest form, science represents a search for answers. It engages the problem of knowledge, an aspect of the mystery of consciousness, rather than providing a simple and final model of reality"--Book jacket.